Trauma-informed assessment with children and adolescents : strategies to support clinicians - Kisiel, Cassandra (Concise guides on trauma care book series., 2021)
"This book serves as a practical guide for clinicians and other professionals working with children and adolescents exposed to trauma, offering an overview and rationale for a comprehensive approach to trauma-informed assessment, including key domains and techniques. Building on more than 2 decades of work in collaboration with the National Child Traumatic Stress Network, the authors provide strategies for conducting an effective trauma-informed assessment that can be used in practice to support the treatment planning and intervention process, family engagement and education, and collaboration and advocacy with other providers. As part of APA's Division 56 series, Concise Guides on Trauma Care, the book surveys a range of recommended tools and considerations for selecting and implementing those tools across stages of development and in relation to a child's sociocultural context. The authors also examine challenges that may arise in the context of trauma-informed assessment and suggest approaches to overcome those barriers"--